PROJECT TO CREATE A TILAPIA REFRIGERATOR - Angelelli Lula, Marcelo; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2021)
This project was conceived by four partners, having as main activity the production of tilapia fillet. Taking into account the increase in demand for this type of fish, especially in the Southeast region, with an increase year after year in consumption and production throughout the country. With this, we see a market opportunity to install a slaughterhouse located in the city of Matão, in the interior of São Paulo, the slaughterhouse will have a unique fillet production, increasing the level and variety of fish, and developing by-products.
Keywords: Fish; Filet; Tilápia